The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/pcmr.12943
|View full text |Cite
|
Sign up to set email alerts
|

Transient activation of tumoral DNA damage tolerance pathway coupled with immune checkpoint blockade exerts durable tumor regression in mouse melanoma

Abstract: Major advances in cancer therapy rely on engagement of the patient’s immune system and suppression of mechanisms that impede the antitumor immune response. Among the most notable is immune checkpoint blockade (ICB) therapy that releases immune cells from suppression. Although ICB has had significant success particularly in melanoma, it eradicates tumors in subsets of patients and sequencing data across different cancers suggest that tumors with high mutational loads are more likely to respond to ICB. This is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…Importantly, in the YUMM1.7-CM tumor-bearing mice/ ICB treatment group, nearly all tumors regressed, while growth of YUMM1.7 tumors was not suppressed by the ICB regimen (Figure 8B). This is consistent with our earlier findings, that demonstrated that a combination protocol that includes ICB in conjunction with intratumoral cisplatin delivery is required for eradication of YUMM1.7 melanoma tumors (13).…”
Section: Features Of Yumm17-cm Clone Generated By In Vitro Exposure To Cisplatinsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, in the YUMM1.7-CM tumor-bearing mice/ ICB treatment group, nearly all tumors regressed, while growth of YUMM1.7 tumors was not suppressed by the ICB regimen (Figure 8B). This is consistent with our earlier findings, that demonstrated that a combination protocol that includes ICB in conjunction with intratumoral cisplatin delivery is required for eradication of YUMM1.7 melanoma tumors (13).…”
Section: Features Of Yumm17-cm Clone Generated By In Vitro Exposure To Cisplatinsupporting
confidence: 93%
“…Female 8–10-week-old C57BL/6 mice were purchased from Envigo (USA) and acclimated for 2 weeks. YUMM1.7 or YUMM1.7-CM tumors were generated by subcutaneous inoculation of 5 × 10 4 cells suspended in a 2:1 PBS/solubilized Matrigel Membrane Matrix (#354234 Corning) into upper left hindlimb as we described ( 13 ). Tumor dimensions were recorded 3×/week using vernier calipers and the formula: volume = ([length] × [width] 2 )/2 to calculate the volume ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this possibility, a previous report has highlighted an important role of Polκ in sustaining resistance to the alkylating agent temozolomide in glioblastoma through activation of the ATR/Chk1 pathway [ 89 ], confirming a previous observation implicating Polκ in Chk1 phosphorylation [ 38 ]. Finally, upregulation of TLS Pols coupled with immunocheckpoint blockade has been reported to improve tumor regression upon treatment with cisplatin [ 90 ]. Altogether, these observations put TLS as an emerging appealing pathway to sensitize cancer cells to the therapy.…”
Section: The Crucial Role Of Tls To Tolerate Structural Impediments During Dna Replicationmentioning
confidence: 99%
“…This partial response may be explained by the low mutational burden encountered in MM. According to data available in other cancers, such as melanoma or non-small cell lung cancer (NSCLC), responders to ICI therapy typically present high numbers of somatic mutations in genomic coding regions [25,26]. The underlying prediction is that mutated genes generate altered-self proteins that can be processed in the form of small peptides, referred to as neoantigens, and presented on the major histocompatibility complex I (MHC-I) molecules at the surface of tumor cells.…”
Section: Immune Checkpoint Blockade Therapy Requires Altered-self Antigensmentioning
confidence: 99%